Indian Women in Technology: An Empirical Analysis of Role Conflict (Malaysian Management Journal, 2013)
An important issue that our society has been facing in the recent past is the changing work and family roles of Indian women. Woman, today, function within multiple roles simultaneously operating in both work and family domains as a mother, spouse, housekeeper, as well as maintaining full-time employment outside the home. The relationship between these dual roles has thus become a topic of interest among organizational researchers. This study deals with selected antecedents and their influence on the role conflict among Indian women in technology. A sample size of 598 Indian women in technology was taken for the study and the result shows the occurrence of work-family conflict. Three predominant factors that influence the work-family conflict time-dimension are work exhaustion, work thought interference and perceived workload in the order of merit.